Floral biology of Stachytarpheta maximiliani Scham. (Verbenaceae) and its floral visitors - Barbola,Ivana de Freitas (2006)
This study describes the reproductive system of Stachytarpheta maximiliani (Verbenaceae), including its floral biology, nectar and pollen availability and insect foraging patterns, identifying whose species act as pollinators. It was carried out in a Brazilian Atlantic rain forest site. Observations on the pollination biology of the Verbenaceae S. maximiliani indicate that their flowering period extends from September through May. Anthesis occurs from 5:30 a.m. to 5:00 p.m. and nectar and pollen are available during all the anthesis. Many species of beetles, hemipterans, flies, wasps, bees and butterflies visit their flowers, but bees and butterflies are the most frequent visitors. The flowers are generally small, gathered in dense showy inflorescences. A complex of floral characteristcs, such as violet-blue color of flowers, long floral tubes, without scents, nectar not exposed, high concentration of sugar in nectar (about 32%), allowed identification of floral syndromes (melittophily and psicophily) and function for each visitor. The bees, Bombus morio, B. atratus, Trigonopedia ferruginea, Xylocopa brasilianorum and Apis mellifera and the butterflies Corticea mendica mendica, Corticea sp., Vehilius clavicula, Urbanus simplicius, U. teleus and Heraclides thoas brasiliensis, are the most important pollinators.